THE EFFECT OF ECONOMIC GROWTH AND THE NUMBER OF POPULATION TO THE UNEMPLOYMENT RATE IN INDRAGIRI HULU REGENCY - Aris Triyono (LPPM Press STIE Indragiri Rengat, 2020)
The research location used as the object of this research is the Central Statistics Agency of Indragiri Hulu Regency. This study aims to determine the effect of economic growth and population simultaneously on the unemployment rate, to determine the effect of economic growth partially on the unemployment rate, to determine the effect of the total population partially on the unemployment rate in Indragiri Hulu Regency. The type of data used in this study is secondary data. The analytical method used is multiple linear regression methods, with the help of SPSS version 21. Based on the results of simultaneous economic growth and population growth has a significant effect on the unemployment rate, economic growth has a partially positive and significant effect on the unemployment rate, the population has a partially positive and significant effect on the unemployment rate, and other variables affect the unemployment rate that is not examined in research